COVID-19 PANDEMIC'S IMPACT ON THE DRUG MANAGEMENT AND DRUG AVAILABILITY AT PUUWATU HEALTH CENTER, KENDARI CITY - Sabarudin Sabarudin; Sunandar Ihsan; Henny Kasmawati; Rifa’atul Mahmudah; Eka Pebriana (Jurnal Farmasi Sains dan Praktis, 2021)
The impact of Corona Virus Disease-19 or COVID-19 pandemic was seen almost all aspects, especially in health facilities. Puskesmas as known as Public Health Center is a primary health service facility that usually became the first choice for seeking treatment so that Puskesmas can be said to be the backbone in facing and fighting the COVID-19 outbreak. This study aimed to determine the impact of the Covid-19 pandemic on drug management and the level of drug availability at Puuwatu Public Health Center, Kendari City. This study was descriptive-evaluative research with quantitative and qualitative methods and retrospective data collection in 2019 (before the pandemic) and 2020 (during the pandemic). Based on the results of the study, the percentage of the suitability of items with National Formulary increased by 1.3% during the pandemic, the percentage of the empty stock increased by 9.8%, the percentage value of damaged and expired items increased by 1.73%, the percentage of less stock decreased by 6, 43%, the percentage of safe stock and excess stock items decreased by 2.36% and 1.06%, respectively. The percentage value of suitability of the physical number of items did not change both in 2019 and in 2020 at the Puuwatu Health Center, Kendari City